THE IMPACT OF MOTIVATION, PARTICIPATION AND COMPETENCE OF EMPLOYEE PERFORMANCE IN FOOD SECURITY AND AGRICULTURAL EXTENSION OFFICE OF EAST BOLAANG MONGONDOW DISTRICT - Tarandung, Chrys D.T (Jurnal Berkala Ilmiah Efisiensi, 2016)
The role of agricultural extension workers is important, in order to increase agricultural output. Therefore the placement of employees as agricultural extension workers should be considered as good as possible. There are several variables that allegedly affect the performance of employees within the institution. The variables in question include motivation, employee participation, and competence. These variables are thought to have a fairly significant effect on the performance of employees in state-owned institutions. This study uses associative with Regression analysis techniques, and classical assumption that include normality, multicollinearity, and heteroscedasticity. 77 employees of the agency food security and agricultural extension, Bolaang Mongondow Timur were survey as samples. The data were analyzed by SPSS software with multiple regression analysis. The results showed that motivation, participation and competence significantly effect on the performance of employees at the Department of Agriculture Food Security and Agricultural Extension Bolaang Mongondow Timur.